Challenges and bottlenecks for butterfly conservation in a highly anthropogenic region: Europe's worst case scenario revisited. (October 2022) - Maes, Dirk; Van Calster, Hans; Herremans, Marc; Van Dyck, Hans
Abstract: The recent decline in insect diversity and abundance and the consequences for associated ecosystem functioning and services have attracted growing attention. Especially highly anthropogenic regions are affected by rapid biodiversity changes including significant losses. Two decades ago, we suggested that Flanders (northern Belgium) was Europe's worst case scenario for butterfly diversity loss with habitat destruction, fragmentation and nitrogen deposition as major causes (Maes and Van Dyck, 2001). To analyse changes since the second half of the 20th century, we used >2.5 million distribution records to calculate trends in distribution during the last three decades. By linking these trends to the species' ecology using multi-species indicators for a set of ecological and life-history traits, we determined the most important drivers policy makers and nature managers should focus on. Species showing the strongest expansion are woodland specialists and polyphagous species. On the other hand, sedentary species of nutrient-poor biotopes such as heathlands and semi-natural grasslands showed a decreasing trend, despite the ongoing policy focus and conservation efforts. We discuss our results with regard to challenges and bottlenecks for the conservation of butterflies and other insects in anthropogenic regions. Graphical abstract: Multispecies Change Indices (MSCI ± se) for biotope preference of butterflies in three decades compared to a reference period (1951–1990). On average, specialist species of heathlands showed a continuous decline compared to the reference period 1951–1990. Specialist species of woodlands, on the other hand, showed a continuous increase since the period 1951–1990. The dashed lines indicate the (arbitrary) thresholds for increases (+100 %) or decreases (−50 %) compared to the reference period 1951–1990. The figures in grey indicate the number of species in each period and each biotope class. The grey dots indicate the mean MSCI and the trend is given in white in the dots: + = increase, +∼ = moderate increase, ∼ = stable, −∼ = moderate decrease, − = decrease, ?+ = potential increase, ?− = potential decrease. Unlabelled Image